Figuring Jerusalem: Politics and Poetics in the Sacred Center - Ezraḥi, Sidrah Deḳoven (University of Chicago Press, 2022)
Intro -- Contents -- List of Figures -- Note on Hebrew Transliteration -- Prologue "Why Jerusalem?" The Politics of Poetry -- Introduction "This House, which is called by My Name" -- Part I. Literary Archaeologies -- 1. "Yes, you did laugh!": The Secret of the Akeda -- 2. "You are as majestic as Jerusalem": The Song and the City -- 3. "Apples of gold in ornaments of silver": Maimonides's Guide to the Poetic Imagination -- Part II. Agnon's Dilemma -- 4. "What may this be likened to?": Agnon and the Poetics of Space -- 5. "Every day I have regretted not having stood in the breach": Agnon in Jerusalem -- Part III. Amichai in the Breach -- 6. "He comes out of a swimming pool or the sea... and he laughs and blesses": Yehuda Amichai, Poet of the Sacred Quotidian -- 7. "Visit my tears and the east wind, which is the true Western Wall": Amichai in Jerusalem -- Coda -- Acknowledgments: Ancient Debts and Ongoing Gratitude -- Notes -- Bibliography -- Index of Names -- Index of Biblical Citations.